Cost-Effectiveness of Apomorphine Sublingual Film as an “On-Demand” Treatment for “OFF” Episodes in Patients with Parkinson's Disease - Andrew Thach; Noam Kirson; Miriam L. Zichlin; Ibrahima Dieye; Eric Pappert; G. Rhys Williams (Journal of Health Economics and Outcomes Research)
**Background:** “On-demand” treatments approved in the United States (US) for “OFF” episodes in Parkinson’s disease (PD) include apomorphine hydrochloride injection (SC-APO), apomorphine sublingual film (APL), and levodopa inhalation powder (CVT-301). APL received US approval in 2020, and its cost-effectiveness has not been compared with SC-APO and CVT-301.